Novel poly(3‐hydroxybutyrate) composite films containing bioactive glass nanoparticles for wound healing applications. Issue 6 (29th April 2016) - Francis, Lydia; Meng, Decheng; Locke, Ian C; Knowles, Jonathan C; Mordan, Nicola; Salih, Vehid; Boccaccini, Aldo R; Roy, Ipsita
Abstract : Novel poly(3‐hydroxybutyrate) (P(3HB)) composite microsphere films containing bioactive glass nanoparticles (n‐BG) were developed for wound healing applications. The effect of the presence of n‐BG and the roughness caused by the formation of hydroxyapatite after simulated body fluid immersion was studied. Abstract: Bioactive glass is considered an ideal material for haemostasis as it releases Ca 2+ ions upon hydration, which is required to support thrombosis. In this study the effects of the presence of nanoscaled bioactive glass (n‐BG) in poly(3‐hydroxybutyrate) (P(3HB)) microsphere films on the structural properties, thermal properties and biocompatibility of the films were studied. The n‐BG with a high surface area was also tested for its in vitro haemostatic efficacy and was found to be able to successfully reduce clot detection time. In an effort to study the effect of the roughness induced by the formation of hydroxyapatite on cellular functions such as cell adhesion, cell mobility and cell differentiation, the composite films were immersed in simulated body fluid for periods of 1, 3 and 7 days. From scanning electron microscopy images, the surface of the P(3HB)/n‐BG composite microsphere films appeared fairly uniform and smooth on day 1; however on day 3 and day 7 a rough and uneven surface was observed. The presence of hydroxyapatite on the composite microsphere films on day 3 and day 7 influenced the surface roughness of the films. However, when the P(3HB)/n‐BG composite microsphere films with enhanced surface roughness were tested for biocompatibility, reduced amounts of protein adsorption and cell adhesion were observed. This study thus revealed that there is an optimal surface roughness for the P(3HB) microsphere films for increased cell adhesion, beyond which it could be deleterious for cell adhesion and differentiation. © 2016 Society of Chemical Industry